Nanoporous GeO2/Cu/Cu2O network synthesized by dealloying method for stable Li-ion storage - Bakenov, Zhumabay; Zhang, Yongguang; Wang, Zhifeng; Zhang, Xiaomin; Yan, Yonghui; Wang, Yichao (Elsevier, 2019)
Transition metal oxide Cu2O anode is still not meeting the current market demands due to the low theoretical capacity and poor cycle stability. We herein report the synthesis of a nanoporous GeO2/Cu/ Cu2O network by a straightforward dealloying method. The resulting material possesses high porosity which served to alleviate the stress incurred during lithiation/delithiation volume variation and presents good conductivity for fast electron transfer. Enhanced electrochemical performance is observed when measured as an anode material, delivering 715mAh g1 at 200mA g1 after 50 cycles and offered 504mAh g1 even at a high current density of 1600 mA g1 after 150 cycles. Furthermore, the material also demonstrates excellent rate performance of 812, 782, 741, 695, 635 and 552 mAh g1 at 100, 200, 500, 800, 1600 and 3200 mA g1 current densities, respectively. The enhanced Li storage performances could be ascribed to the reticular ligament with high porosity, the increased conductivity by Cu as well as the improved capacity from GeO2. Moreover, this work provides us a new material design strategy to fabricate various porous composite anodes with high capacity through a straightforward dealloying method in future for lithium-ion battery applications.